창업 및 재취업 교육이 재취업불안, 재취업스트레스, 창업의도에 미치는 영향 - 김서호(Kim, Seo-ho); 변상해(Byun, Sang hae) (벤처창업연구, 2016)
Sothe Korea that entered in to aging society in year 2000 according to the entrance in 2017 as in log-term the young work focrce decrease and skilled elder populatin decrease became important issue of national entrepreneurship & re-employment of middle-age' has become the topic of social problems. The purpose of this study was to examine the impact of a entrepreneurship & re-employment education to job-seeking anxiety, job-seeking stress and entrepreneurial intention in an effort to prove the effectiveness of entrepreneurship & re-employment education. The subjects in this study were 67 believer who were of G church in the city of K. A entrepreneurship & re-employment education was conducted in fourteen sessions, once a week. The major findings of the study were as follows: First, the experimental group who participated in the entrepreneurship & re-employment education felt less job-seeking anxiety. Second, the experimental group who participated in the entrepreneurship & re-employment education felt less job-seeking stress. Third, the experimental group who participated in the entrepreneurship & re-employment education showed improvement in entrepreneurial intention. 2000년에 접어들어 고령화 사회로 진임하게 된 대한민국은 2017년 고령사회로의 진입하게 됨에 따라 장기적으로 청년 노동력의 감소와 그로인한 숙련된 중장년 및 고령인구의 감소가 국가경제의 중요이수로 부각되고 있다. 따라서 은퇴 및 실직자들의 창업 및 재취업이 사회의 중요한 화두가 되고 있다. 본 연구는 중년기를 위한 창업 및 재취업교육이 재취업불안, 재취업스트레스 그리고 창업의도에 미치는 영향을 분석하고자 실시하였다. K에 소재한 G교회에 출석중인 은퇴자 67명을 선정한 후 각각 실험집단 32명과 통제집단 35명으로 구분하였다. 매주 1회 총 13회기의 창업 및 재취업교육을 실시하였으며, 본 연구에서 나타난 주요 결과를 요약하여 제시하면 다음과 같다. 첫째, 창업 및 재취업 교육에 참여한 실험집단은 참여하지 않은 통제집단보다 재취업불안이 감소되었다. 둘째, 창업 및 재취업 교육에 참여한 실험집단은 참여하지 않은 통제집단보다 재취업스트레스가 감소되었다. 셋째, 창업 및 재취업 교육에 참여한 실험집단은 참여하지 않은 통제집단보다 창업의도가 향상되었다.